Elucidating the role of seed structure in the heterometallic seeded growth of copper-based nanocrystals - Jeong, Soojin; Skalla, Rebecca X.; Wang, Yi; Zhu, Baixu; Ye, Xingchen (Frontiers in Nanotechnology, 2023)
Seed-mediated synthesis is a versatile method to prepare multimetallic nanocrystals for diverse applications. However, many fundamental questions remain on how the structural and chemical properties of nanocrystal seeds control the reaction pathways, especially for nonaqueous synthesis at elevated temperatures. Herein, we elucidate the role of surface ligands and crystallinity of Au nanocrystal seeds on the heterometallic seeded growth of Cu-based nanocrystals. We found that weakly coordinating ligands are critical to facilitate the diffusion between Au and Cu which enables subsequent one-dimensional growth of Cu. Replacing multiple-twinned Au seeds with single-crystalline ones switched the growth pathway to produce heterostructured nanocrystals. Our work illustrates the importance of precise control of seed characteristics for predictive synthesis of structurally complex multimetallic nanocrystals.